Multi-Omics Approaches Unravel Specific Features of Embryo and Endosperm in Rice Seed Germination - Sano, Naoto; Lounifi, Imen; Cueff, Gwendal; Collet, Boris; Clément, Gilles; Balzergue, Sandrine; Huguet, Stéphanie; Valot, Benoît; Galland, Marc; Rajjou, Loïc (Frontiers in Plant Science, 2022)
Seed germination and subsequent seedling growth affect the final yield and quality of the crop. Seed germination is defined as a series of processes that begins with water uptake by a quiescent dry seed and ends with the elongation of embryonic axis. Rice is a key crop species, and during seed germination, two tissues function in a different manner; the embryo grows into a seedling as the next generation and the endosperm is responsible for nutritional supply. Toward understanding the integrated roles of each tissue at the transcriptional, translational, and metabolic production levels during germination, an exhaustive “multi-omics” analysis was performed by combining transcriptomics, label-free shotgun proteomics and metabolomics on rice germinating embryo and endosperm, independently. This work illustrates the different roles played by seed compartments during germination. In endosperm, protein profiles mostly showed abundance decreases corresponding to 90% of the differentially accumulated proteins. An ontological classification revealed the shift from the maturation to the germination process where over represented classes belonged to embryonic development and cellular processing classes. In embryo, 19% of the detected proteins are differentially accumulated during germination. Stress response and carbohydrate metabolism are the main functional classes representing embryo proteome change. Moreover, proteins specific of the germinated state uncovered a major change in the rice seed biology and the participation of networks operating during rice germination. In particular, concomitant changes of hormonal metabolism-related proteins (GID1L2 and CNX1) implicated in GAs and ABA metabolism, signaling proteins, protein turnover events emphasized the importance of such biological networks. Using metabolomics, we highlighted the importance of energetic supply in rice seeds during germination. In both embryo and endosperm, starch degradation, glycolysis and subsequent pathways related to these cascades such as the aspartate-family pathway are activated during germination. A relevant number of accumulated proteins and metabolites, especially in embryos testifies the pivotal role of energetic supply in preparation of plant growth. This work summarizes the key genetic pathways in embryo and endosperm during rice seed germination at the transcriptional, translational and metabolite levels and thereby, emphasizes the value of combined multi-omics approaches to uncover the specific feature of tissues during germination.